Trabalho associativo, identidades territoriais e desenvolvimento sustentável: O caso da Associaç\~ao de Apicultores da regi\~ao do Alto Turi Maranhense - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This research aimed to analyze the mechanisms of social organization and collective action around projects associative of solidarity economy and territorial development. For this, the empirical element analysis will be the Beekeepers Association of the Region of Alto Turi Maranhense (Turimel), formed in 2008 by a group of farming families who reside in a state with a region of origin in the 1960s, but until today remains serious problems regarding infrastructure, public services and property rights. Dealing with the difficulties and feasibility of this collective project resulted in the institutional recognition of Turimel and empowerment of the families involved, as well as improving their quality of life. More than an economic enterprise, the beekeeping associative was a strong element of re-territorialization in the Alto Turi, since it allowed an environment of new prospects for productive insertion its rural population, while it opened other fields dispute from a new economic dynamic market.
Keywords: Q13; R52; 330; associations; family farming; territorial development; solidarity economy; identity; beekeeping